Effect of Sea Buckthorn and Vitamin E on Growth Performance of Acipenser stellatus (Pallas 1771) Juveniles - Oana-Georgiana (Varlan) Dorojan; Victor Cristea; Mirela Creţu; Lorena Dediu; Iulia Rodica Grecu; Săndiţa Plăcintă (Scientific Papers Animal Science and Biotechnologies, 2023)
Addition of natural additives (prebiotics, probiotics, phytobiotics) in fish feed is a benefic method because it leads to improved growth performance of fish reared in intensive production systems. Sea buckthorn is one of the most commonly phytobiotics used in aquaculture because of its antioxidant, antimicrobial, immunostimulant, anti-stress, cytoprotective, liver and tissue regeneration properties. Sea buckthorn berries are rich in vitamins (B, C, E and K), flavonoids, carotenoids, tocopherols and many volatile compounds. In this context the aim of this study was to evaluate the effects of dietary vitamin E (500 mg/kg diet) and sea buckthorn on growth performance and survival of the A. stellatus juveniles reared in a recirculating aquaculture system. The experiment took place in the recirculating pilot system of “Dunărea de Jos” University of Galaţi. In order to emphasize the influence of the above mentioned immunostimulants on sevruga fingerlings with different genetic background, four experimental groups from different genitors (V1: ♀2 Danube x ♂1 Aquaculture, V2: ♀1 Danube x ♂1 Danube, V3: ♀1 Danube x ♂2 Aquaculture and V4: ♀2 Danube x ♂2 Danube) have been used. At the end of the experiment no significant differences (p>0.05) were observed in terms of final mean weight, individual growth rate, SGR, FCR, PER, between the sevruga fingerlings obtained from wild genitors, comparing with those obtained from aquaculture genitors.